ANALISIS PERDAGANGAN BAGIAN TUBUH HEWAN MAMALIA DILINDUNGI PADA E-COMMERCE - Amalia, Risqi; Cahyanto, Tri (JURNAL HUTAN LESTARI, 2023)
The trade of protected wildlife violates biodiversity. High demand has driven illegal traders to explore new avenues through e-commerce. Despite government efforts to address this issue, the trade remains rampant. This research analyzes the trade of parts of protected mammalian species on e-commerce platforms. Through a desk study method, data indicates five mammalian species, such as deer, tigers, elephants, rhinos, and leopards, are preserved for decorative purposes. Tokopedia, Shopee, Facebook, and Bukalapak are the primary marketplaces. Tokopedia has the highest number of products from protected mammalian species due to inadequate supervision. Commonly found products include wall decorations made from the heads of deer, sought after for the uniqueness of their antlers. The government has enacted Law No. 5 of 1990 on the Conservation of Natural Resources and Ecosystems (KSDAE) and Regulation No. 7 of 1997 on wild animals, but implementation has been hindered. Significant efforts are needed to enforce regulations for better conservation of natural resources.Keywords: Animal, protected, trade, e-commerce, Tokopedia.AbstrakPerdagangan satwa dilindungi melanggar keberagaman hayati. Tingginya permintaan mendorong pedagang ilegal mencari cara baru melalui e-commerce. Pemerintah berupaya mengatasi hal ini, namun perdagangan tetap tinggi. Penelitian ini menganalisis perdagangan bagian tubuh hewan mamalia dilindungi di e-commerce. Melalui metode desk study, data menunjukkan lima jenis mamalia seperti rusa, harimau, gajah, badak, dan macan tutul yang diawetkan untuk hiasan. Tokopedia, Shopee, Facebook, dan Bukalapak adalah marketplace utama. Tokopedia memiliki produk bagian tubuh hewan mamalia dilindungi terbanyak karena pengawasan yang kurang. Produk yang umum ditemui adalah hiasan dinding dari kepala rusa yang diminati karena keunikan tanduknya. Pemerintah telah mengeluarkan Undang-Undang No 5 Tahun 1990 tentang Konservasi Sumber Daya Alam dan Ekosistem (KSDAE) dan PP No 7 Tahun 1997 tentang satwa liar, namun implementasinya terhambat. Diperlukan usaha keras untuk menegakkan peraturan guna menjaga konservasi sumber daya alam dengan lebih baik.Kata Kunci: Satwa, dilindungi, perdagangan, e-commerce, Tokopedia.